The Effect of Entrepreneurial Competence Entrepreneurial Orientation and Information Technology Utilization on Business Performance through Competitive Advantage in Handicraft Businesses Assisted by the Medan City SME Cooperative Office - Nasution, Muhammad Azhar; Dalimunthe, Ritha F.; Siahaan, Elisabet (PT FORMOSA CENDEKIA GLOBAL, 2024)
Micro, small, and medium enterprises are the main pillars of economic development. The existence of MSMEs in Medan City is still vulnerable to various factors that affect performance. MSMEs often need help with entrepreneurial competence, entrepreneurial orientation, and utilization of information technology, which impact low competitive advantage. This research aims to analyze entrepreneurial competence, entrepreneurial orientation, and utilization of information technology on business performance through competitive advantage in handicraft businesses assisted by the Office of SME Cooperatives, Industry and Trade of Medan City. This study uses a quantitative approach as a research method. The population in this study were handicraft business actors assisted by the Office of SME Cooperatives, Industry, and Trade of Medan City, totaling 95 respondents—data analysis using descriptive statistical analysis techniques and path analysis using Smart PLS. The results showed that Entrepreneurial Competence, Entrepreneurial Orientation, and Information Technology Utilization on Performance through Competitive Advantage in Handicraft Businesses Assisted by the Office of Cooperatives, SMEs, Industry, and Trade of Medan City all research variables have a positive and significant influence variables.